Analysis of Waiting Time and Outpatient Satisfaction on the Use of APM Machines for Online Reservations at Bandung City Hospital - Annisa Ulfah; Gusti Basyiro Afwana (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: The adoption of digital technologies in hospital services is an important step toward improving patient flow and administrative efficiency. Self-Service Registration Machines (APM) offer an alternative to conventional queuing systems that often lead to delays and patient dissatisfaction. Objectives: This study aims to evaluate the impact of APM integrated with the Pangestu online reservation system on outpatient waiting time, patient satisfaction, and administrative workflow at Bandung City Hospital. Methods: A descriptive qualitative design was applied using three data collection methods: participatory observation, semi-structured interviews with 15 respondents from different age groups, and analysis of hospital documentation. Results: The use of APM reduced average registration time from 15–30 minutes (manual) to 2–5 minutes. Patients, especially millennials, expressed high satisfaction with the speed and ease of use of the system, while older adults required assistance. Administrative staff reported reduced workload and improved focus on complex tasks. System integration with SIMRS ensured data accuracy and service continuity. Conclusions: APM improves the efficiency of outpatient registration services, enhances patient experience, and contributes to a more responsive and sustainable digital health system. Its scalability to other service units such as pharmacy, laboratory, and inpatient departments is highly recommended.